Development of thermohydraulic models of core elements of “Neutron source” - Kukhotsky, O.V.; Nosovsky, A.V.; Dybach, O.M. (Вопросы атомной науки и техники, 2017)
This article focuses on the development of independent thermohydraulic models of the core elements of the research nuclear subcritical facility. Its design and construction is currently being implemented by the National Science Center “Kharkov Institute of Physics and Technology”. The article describes the process of modeling neutron-generating target and the fuel assembly of “Neutron Source”. Moreover, the results of the verification calculations of the developed models are also clarified. These models are unique, because they were made for the first time for the key elements of subcritical facility using CFD code ANSYS CFX.